A Study On Measurement Of Transverse Internal Diameter Of Trachea At C6 Vertebral Level By Computed Tomography And Its Clinical Implications (Journal of Pharmaceutical Negative Results, 2023)
Aim: To study the measurement of transverse internal diameter of trachea by CT scan in patients and to compare the parameters between males and females.Methods: This prospective study performed at Bankura Sammilani Medical College, Bankura, India, over a period of 1 year and 6 months from January 2015 to June 2016. 100 patients were selected among which 63 were male and 37 were female.Results: Data of 100 participants were analysed out of which 63%were males &37% were female.Majority (35%) of study subjects belonged to the age group of 11-20 years. From the results of the ananlysisit was clear that the influence of gender was found to be consistent throughout all the age groups i.e. female had a comparatively lower TIDT than that of the male. Scatter plot/Dot diagram between age and TIDT for the higher age group was revealed to be helpful for us to understand the influence of age on TIDT in the higher age group. It showed that only 3 percent variation in outcome variable (TIDT) could be explained by variation in input variable (age). Straightline equation (y=1.28+9.61E-4*x) showing a huge error component (E) indicated that in this age group role of age on TIDT was insignificant. Age played a positive role in the TIDT up to the age of 21 years and gender was shown to have role in all age groups.Conclusion: CT is a relatively accurate and safe way to measure the transverse internal diameter of the trachea.